Experimental Study of the Stress State of a Polymer Composite in a State of Compression - Anatoliy Ishchenko; Volodymyr Kravchenko; Artem Arustamian; Dmytro Rassokhin; Dimitrij Seibert; Olena Nosovska; Robert Böhm; Stanislav Kapustin (Applied Mechanics)
Long-term operation of the supporting surfaces of large-sized parts, in particular tubular units of thermal power plants, leads to the destruction of the contact surfaces. Moisture penetrates into the formed discontinuities, and the vibrations present in the equipment in use rapidly increase the gap, reaching values of 10–15 mm. The authors of this article proposed the application of a composite layer of multimetal 1018 material without performing additional preparatory operations, ensuring the mandatory penetration of the material into the body of the supporting surface. This depth provides additional stability by maintaining boundary conditions. To determine the rational thickness of the composite layer, mathematical modeling of static loading of samples with different thicknesses in a wide range of values (from 2 mm to 12 mm) was performed. It was determined that the effective implementation of the developed technology was possible due to an increase in the load-bearing capacity of the composite material by creating additional grooves, or artificially creating grooves by welding, in the body of the part with a depth of 2.5–3 mm. The optimal excess of the composite was 1.0–1.5 mm. The proposed technology increases the stability of the composite layer up to three times and allows restoration without the use of mechanical treatment. The increase in the maximum stress values was 770 MPa, compared to the standard technology of 205 MPa.